PENGARUH KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN DI HOTEL GRAND ROCKY BUKITTINGGI - Rahman, Hidayatur; Chair, Ira Meirina; Abrian, Youmil (Journal of Home Economics and Tourism, 2017)
The purpose of research is to determine the effects of compensation on employee job satisfaction at Grand Rocky Hotel Bukittinggi. The research is associative causal research With a population of all employee Grand Rocky Hotel Bukittinggi with status permanent and contract , amounting to 112 employees. The selection of the study sample using nonprobability with sample of 87 employee are taken purposive sampling. Collecting data using a questionnaire based on Likert Scale which has been tested for validity and reliability. The study concluded that the overall compensation belong to the category of a very good with the percentage 55,17% and job satisfaction too belong to the category of a very good with the percentage 64,36%. These results indicate a positive and significant influence between compensation and employee job satisfaction at Grand Rocky hotel Bukittinggi where the value of 21.970 t> t table 1.662. Thus Ha stating there is influence between compensation and job satisfaction can be received with great influence of 85%, while 15% were job satisfaction is influenced by other factors.Key words: compensation and job satisfaction.